Quality of life in breast cancer survivors - Costa,Weruska Alcoforado (2017)
Summary Objective: To evaluate the influence of functional capacity (FC) and how it affects quality of life (QoL) in breast cancer survivors. Method: A total of 400 breast cancer survivors were studied - 118 without metastasis, 160 with locoregional metastasis and 122 with distant metastasis. The European Organization for Research and Treatment for Cancer Quality of Life Questionnaire--Core 30 (EORTC QLQ-C30), Breast Cancer-Specific (EORTC QLQ-BR23), and the Karnofsky Performance Scale (KPS) were used to evaluate FC and QoL. Results: Women with distant metastases presented lower KPS 75.3 (SD=12.5) (p<0.001). For QLQ-C30, the mean of the Functional Scale for patients with distant metastasis was 57 (SD=19) (p<0.001), and the mean of the Symptom Scale for patients with distant metastasis was 37 (SD=20) (p<0.001). Both the scales for pain and fatigue showed the highest mean in the groups. For the Global Health Scale, patients without metastasis scored a mean of 62 (SD=24) points, while those with locoregional metastases scored a mean of 63 (SD=21.4), and distant metastasis scored 51.3 (SD=24) points. In the group with distant metastases, 105 (87%) had pain, and the average KPS was 74 (SD=12.0) (p=0.001). Conclusion: Breast cancer was associated with decreased FC, compromised QoL in women with locoregional and distant metastases compared to those without metastasis.